The Preeclampsia - the leading cause of maternal and neonatal mortality in the world - review of literature - Staszczak, Paweł; Różańska-Smuszkiewicz, Gabriela; Smuszkiewicz-Różański, Paweł; Jaworska, Barbara; Kmiotek, Weronika; Oronowicz, Radosław; Ragan, Dagmara; Pażyra, Aldona; Kusak, Natalia; Żak, Natalia; et al. (Quality in Sport, 2024)
Background: This review analyzes current knowledge on the pathophysiology, prevention and art of treatment of preeclampsia. Preeclampsia (known as EPH-gestosis) is nowadays the leading cause of maternal and neonatal mortality in the world. According to statistics it affects up to 5% of pregnant women. The symptoms are high blood pressure, edema, proteinuria. The scientists all over the world are trying their best to know the pathogenesis to devise a cure for the disease. Aim of study: The goal of this article was to gather information about the pathophisiology and treatment of preeclempsia to prevent the risk of ilness’ development. Materials and methods: A review of the literature available in the “PubMed”, Google Scholar and Medline databases. The search was performed by using following keywords: “preeclampsia”, “ophthalmic artery doppler”, “PIGF”, “aspirin”, “placenta”. Results and conclusions: In spite of the progress of science the preeclampsia is still a serious threat for pregnant women all around the world. Thank to the advanced molecular and ultrasonographic techniques the doctors can estimate the risk of complications. The most important is screening, which helps the doctors to define the group of risk and then launch the treatment. That should decrease the amount of maternal and neonatal complications and deaths.